Numerical simulation of high-intensity metal ion beam generation; Journal of Physics: Conference Series; Vol. 1115 : 6th International Congress "Energy Fluxes and Radiation Effects". 14th International Conference on Modification of Materials with Particle Beams and Plasma Flows (14th CMM) - Koval T. V. Tamara Vasilievna; Ryabchikov A. I. Aleksandr Ilyich; Chan My Kim An; Shevelev A. E. Aleksey Eduardovich; Sivin D. O. Denis Olegovich; Ivanova A. I. Anna Ivanovna; Paltsev D. M. Demid Mikhaylovich (2018, 2018)
Title screen